Drug detection dogs at Australian outdoor music festivals: Deterrent, detection and iatrogenic effects - Grigg, Jodie; Barratt, Monica; Lenton, Simon (Elsevier BV, 2018)
© 2018 Elsevier B.V. Background: Recent drug-related deaths at Australian music festivals have led to increasing concern about the risk of future harm, but contention about how to effectively respond. One hotly debated strategy has been the use of drug detection dogs which currently operate at festivals across Australia, despite claims they are ineffective and contribute to risky drug use practices. This paper aims to investigate responses to the expected presence, and sightings, of drug dogs at the last festival attended. Methods: An anonymous online survey was completed by almost 2000 Australian festival-goers. The largest subsample used in the analyses for this paper (n = 647) was 59% male and had a median age of 20 (IQR = 18–22). Results: Of those who expected dogs to be present at their last festival (n = 647), only 4% reported that this threat led them to decide not to take drugs. Other responses included: concealing their drugs well (48%), getting someone else to carry their drugs (15%), buying their drugs inside (11%), taking less easily detected drugs (10%) and taking drugs before entering (7%). Of those who carried drugs in (n = 418), 10% concealed them internally and 1% swallowed them to retrieve inside. Of those who had drugs on their person when seeing a dog (n = 189), 10% reported consuming drugs in response. No respondents reported being detected with drugs due to a positive identification. Conclusion: Almost all festival-goers surveyed did not report being deterred from drug usage by the expected presence of drug dogs. Instead, a variety of alternative responses to avoid detection were reported, many of which could place festival-goers at greater risk of experiencing drug-related harms. In the face of mounting evidence of both ineffectiveness and iatrogenic effects, the use of drug detection dogs at Australian music festivals should be urgently reconsidered.